Global viral hepatitis elimination by the year 2030 - Tjan, Richard (Universa Medicina, 2016)
According to a report by Stanaway et al.(1) in 2016, the absolute burden and relative rank of viral hepatitis increased between 1990 and 2013. For example, the number of global deaths due to viral hepatitis increased from 0.89 million to 1.45 million, indicating a need for its reduction. In this connection, on 28 May 2016 the 69th World Health Assembly adopted the global health sector strategy on viral hepatitis for the period 2016â2021,(2) as outlined in the report A69/32 of the Secretariat,(3) with the goal of eliminating viral hepatitis B and C by the year 2030. The global health sector strategy (GHSS) on viral hepatitis has constructed a roadmap toward the elimination of viral hepatitis B and C, targeting five priority prevention and treatment interventions. Prevention involves universal hepatitis B immunization of infants, prevention of mother-to-child transmission, increased injection safety and blood safety, and increased harm reduction, the implementation of which will contribute toward universal health coverage, which is the target for Goal 3 of the 2030 Agenda for Sustainable Development. In combination with treatment of chronic hepatitis, the goal is to achieve by the year 2030 a reduction in the incidence of viral hepatitis by 90% and mortality by 65%.(3,4)